Respuesta :

Answer:

(B). roots

Step-by-step explanation:

(a ± b)² = a² ± 2ab + b²

~~~~~~~~

( [tex]\sqrt{4x+5}[/tex] - [tex]\sqrt{x-1}[/tex] )² = ( [tex]\sqrt{x+4}[/tex] )²

( [tex]\sqrt{4x+5}[/tex] )² - 2[tex]\sqrt{(4x+5)(x-1)}[/tex] + ( [tex]\sqrt{x-1}[/tex] )² = ( [tex]\sqrt{x+4}[/tex] )²

4x + 5 - 2[tex]\sqrt{(4x+5)(x-1)}[/tex] + x - 1 = x + 4

2[tex]\sqrt{(4x+5)(x-1)}[/tex] = 4x + 5 + x - 1 - x - 4

[tex]\sqrt{(4x+5)(x-1)}[/tex] = 2x

( [tex]\sqrt{(4x+5)(x-1)}[/tex] )² = ( 2x )²

( 4x + 5 )( x - 1 ) = 4x²

4x² + x - 5 = 4x² ⇒ x = 5